Competition, cooperation, and corporate culture - Michael Kosfeld; Ferdinand von Siemens (Institute for the Study of Labor (IZA), 2007)
Teamwork and cooperation between workers can be of substantial value to a firm, yet the level of worker cooperation often varies between individual firms. We show that these differences can be the result of labor market competition if workers have heterogeneous preferences and preferences are private information. In our model there are two types of workers: selfish workers who only respond to monetary incentives, and conditionally cooperative workers who might voluntarily provide team work if their co-workers do the same. We show that there is no pooling in equilibrium, and that workers self-select into firms that differ in their incentives as well as their resulting level of team work. Our model can explain why firms develop different corporate cultures in an ex-ante symmetric environment. Moreover, the results show that, contrary to first intuition, labor market competition does not destroy but may indeed foster within-firm cooperation.
Keywords: 650; Gruppenarbeit; Leistungsmotivation; Arbeitszufriedenheit; Unternehmenskultur; Arbeitsmarkt; Marktmechanismus; Theorie